2004
DOI: 10.1093/ajcn/80.5.1312
|View full text |Cite
|
Sign up to set email alerts
|

Low ratio of S-adenosylmethionine to S-adenosylhomocysteine is associated with vitamin deficiency in Brazilian pregnant women and newborns

Abstract: Lower maternal cobalamin concentrations are associated with higher tHcy and lower SAM:SAH in newborns. Because SAM:SAH is closely linked with the activity of numerous enzymatic methylation reactions, these results suggest that methylation could be impaired in cobalamin-deficient pregnant women and their newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 38 publications
5
36
1
13
Order By: Relevance
“…The results were compared with the 95% confidence intervals reported previously (Guerra-Shinohara et al 2004). The methionine concentration was 35 and 35.5 μmol/L, at most very slightly elevated (reference 95% CI: 25.4−27.3 μmol/L).…”
Section: Case Report: Pretreatment Period In Patient 2 the Younger Bmentioning
confidence: 84%
“…The results were compared with the 95% confidence intervals reported previously (Guerra-Shinohara et al 2004). The methionine concentration was 35 and 35.5 μmol/L, at most very slightly elevated (reference 95% CI: 25.4−27.3 μmol/L).…”
Section: Case Report: Pretreatment Period In Patient 2 the Younger Bmentioning
confidence: 84%
“…Some studies have found that pregnancy may result in impaired methylation and lower levels of SAMe [73], suggesting a potential benefit from SAMe administration in pregnant women. SAMe supplementation in pregnant women with intrahepatic cholestasis has been associated with beneficial effects [74].…”
Section: Recommendations and Special Considerations For Women Who Arementioning
confidence: 99%
“…Vários estudos mostraram correlação inversa entre as concentrações de folato (sérico e eritrocitário) e/ou cobalamina e os valores de tHcy; e entre as concentrações séricas de cobalamina e MMA em gestantes GUERRA-SHINOHARA et al, 2004;MCMULLIN et al ,2001 (ALLEN et al, 1993c;DONNELY, 2003).…”
Section: Marcadores Da Deficiência De Vitaminasunclassified
“…A S-adenosilmetionina (SAM) e a S-adenosilhomocisteína (SAH), bem como a razão SAM/SAH também são consideradas marcadores de deficiência de folato e/ou cobalamina (ALLEN et al, 1993c;GUERRA-SHINOHARA et al, 2004;SAVAGE et al, 1994). Pacientes brasileiros com deficiência grave de cobalamina apresentaram concentrações elevadas de SAH e menor razão SAM/SAH, que foram corrigidos pela administração de cianocobalamina via intramuscular (GUERRA-SHINOHARA et al 2007).…”
Section: Marcadores Da Deficiência De Vitaminasunclassified
See 1 more Smart Citation